Wave current force test of deep water foundation of bridge in marine environment - Li, Ling; Yue, Ling; Xing, Xiao-Fu (Frontiers in Earth Science, 2023)
As a key parameter in the design and construction of the Sea Crossing Bridge, the wave and current load on the pile foundation has been the subject of extensive research. The magnitude and distribution of wave and current loads on pile foundations are crucial for the safety of the foundation. Based on Male Airport Island Bridge Project in the Maldives, the wave current force of platform pile and steel casing in different construction stages is investigated, and the horizontal force and bending moment of the foundation under various wave and current parameters are tested using an indoor model. The results are as follows: (1) With the same effective wave height and wave period, the maximum horizontal force and bending moment on the pile exhibit a linear relationship to the wave velocity. Under the same water depth, the combined wave current force is greater than the sum of wave force and simple current force, with a maximum difference of 70%; (2)Under 2-year return period wave and current conditions, the horizontal stress on a single platform pile and steel casing increases linearly with the increase in height, and there will be nonlinear relationship with 10-year return period wave and current conditions; (3)With more platform piles and steel casing, the front row piles have obvious protective effect on the rear row piles, and the horizontal force and bending moment of the overall structure increase nonlinearly.